CSIG-37. FOXR2 STABILIZES MYC AND ACTIVATES FAK/SRC SIGNALING IN A DUAL MECHANISM TO PROMOTE TRANSFORMATION IN NEURAL PROGENITOR CELLS. (5th November 2018) - Beckmann, Pauline; Larson, Jon; Larsson, Alex; Ostergaard, Jason; Largaespada, David
Abstract: Medulloblastoma and central nervous system primitive neuroectodermal tumors (CNS-PNETs) are aggressive, poorly differentiated brain tumors that primarily affect children. Current treatment strategies with severe long-term treatment-related side effects and poor survival rates warrant further study into therapies with increased efficacy and lower cost to the patient. More targeted therapy represents a route to better treatments, but a barrier to identifying novel targets is a lack of animal models. We created a mouse model that developed medulloblastoma or CNS-PNET using Sleeping Beauty ( SB ) mutagenesis of neural progenitor cells (Nestin+). SB -induced tumors resembled human medulloblastoma and CNS-PNET histology. Additionally, we used RNA-Sequencing to determine that they most closely resemble human SHH, group 3, and group 4 medulloblastoma and a subgroup of CNS-PNET with FOXR2 activation (CNS NB- FOXR2 ).Using both DNA and RNA analysis, we identified over 100 genes as candidate drivers in medulloblastoma and/or CNS-PNET. FOXR2 was identified as a proto-oncogene, with increased expression in SB -induced mouse tumors. FOXR2 drives colony formation in soft agar and tumor formation in vivo when overexpressed in a mouse neural progenitor cell line. We found that FOXR2 binds N-MYC and increases C-MYC stability in 2 neural cell lines. We also found a novel role for FOXR2 in activating the FAK/SRC signaling pathway. Increased FOXR2 drove FAK/SRC activation, in a MYC interaction-independent manner, and FOXR2 KO decreased FAK/SRC activation. Interestingly, increased FOXR2 expression conveyed resistance to a SRC family kinase inhibitor (Dasatinib) in a MYC-dependent manner, indicating overlap between these two apparently distinct effects. Further studies into the mechanism of FOXR2-driven tumorigenesis may provide a novel route for therapy in treating patients with medulloblastoma and CNS-PNET with high FOXR2 levels.